Advances in physicochemical pretreatment strategies for lignocellulose biomass and their effectiveness in bioconversion for biofuel production. (February 2023) - Basak, Bikram; Kumar, Ramesh; Bharadwaj, A.V.S.L. Sai; Kim, Tae Hyun; Kim, Jung Rae; Jang, Min; Oh, Sang-Eun; Roh, Hyun-Seog; Jeon, Byong-Hun
Graphical abstract: Highlights: Emerging physicochemical pretreatments (EPPs) for LCB are discussed. Integrated physicochemical techniques favor LCB fractionation at various levels. Fractionation and delignification of LCB significantly improve its bioconversion. The effects of different EPPs on biofuel production are highlighted. Challenges of the EPPs for sustainable biofuel production are highlighted. Abstract: The inherent recalcitrance of lignocellulosic biomass is a significant barrier to efficient lignocellulosic biorefinery owing to its complex structure and the presence of inhibitory components, primarily lignin. Efficient biomass pretreatment strategies are crucial for fragmentation of lignocellulosic biocomponents, increasing the surface area and solubility of cellulose fibers, and removing or extracting lignin. Conventional pretreatment methods have several disadvantages, such as high operational costs, equipment corrosion, and the generation of toxic byproducts and effluents. In recent years, many emerging single-step, multi-step, and/or combined physicochemical pretreatment regimes have been developed, which are simpler in operation, more economical, and environmentally friendly. Furthermore, many of these combined physicochemical methods improve biomass bioaccessibility and effectively fractionate ∼96 % of lignocellulosic biocomponents into cellulose, hemicellulose, and lignin, thereby allowing for highly efficient lignocellulose bioconversion. This review critically discusses the emerging physicochemical pretreatment methods for efficient lignocellulose bioconversion for biofuel production to address the global energy crisis.